Bone Mineral Density and Vitamin D Status in Patients with Autoimmune Polyglandular Syndromes: A Single Tertiary Care Center Experience - Akkurt Kocaeli, Aysen; Erturk, Erdınc (Hormone and Metabolic Research, 2023)
Immunological abnormalities, the resulting endocrinopathies, and their treatments may impact bone health and 25-hydroxyvitamin D (25-OHD) in patients with autoimmune polyglandular syndromes (APS). Several etiologies contribute to increased risk for low bone mineral density (BMD), including vitamin D deficiency. This study evaluated the vitamin D level and BMD of patients with APS. We performed a cross-sectional study on 44 patients with APS and 55 age and gender-matched control subjects. Among patients with APS, 14 were classified as APS-2 [Addison’s disease (AD)+autoimmune thyroid disease (ATD) and/or type 1 diabetes(T1D)]. In contrast, the other 30 were APS-3 (ATD+T1D+other autoimmune diseases). Serum samples were analyzed for vitamin D levels. The lumbar spine and femoral neck BMD were measured by dual X-ray absorptiometry. Z-scores were obtained by comparison with age- and gender-matched average values (both patients and controls). The accepted normal levels were Z-score>–1 and 25-OHD>30 ng/ml. Patients with APS showed 25-OHD levels and BMD significantly lower than healthy controls (p<0.001 and p<0.05, respectively). The highest prevalence of abnormal BMD was observed in the APS-2 subgroup (13 out of 14 patients, 92.6%). Identifying and treating vitamin D deficiency and low BMD is critical in APS patients. The fact that the significant endocrine component of APS-2 is AD, and these patients receive chronic long-term glucocorticoid therapy can be shown as the reason for this result. However, more extensive prospective controlled studies are needed to confirm these findings.
Keywords: autoimmune polyglandular syndrome; vitamin D deficiency; low bone mineral density; Addison’s disease